2022
DOI: 10.3389/fmed.2022.871229
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinergic Drug Exposure Increases the Risk of Delirium in Older Patients Undergoing Elective Surgery

Abstract: IntroductionPostoperative delirium (POD) is a common and serious adverse event of surgery in older people. Because of its great impact on patients' safety and quality of life, identification of modifiable risk factors could be useful. Although preoperative medication intake is assumed to be an important modifiable risk factor, the impact of anticholinergic drugs on the occurrence of POD seems underestimated in elective surgery. The aim of this study was to investigate the association between preoperative antic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…This anticholinergic activity can be estimated through anticholinergic burden scales. A preoperative high anticholinergic burden is significantly associated with incident delirium [ 40 42 ], although contrary findings with no association have been reported in other studies [ 43 ]. Our study determined that a high anticholinergic burden was significantly associated with POD in both univariable and multivariable analyses.…”
Section: Discussionmentioning
confidence: 98%
“…This anticholinergic activity can be estimated through anticholinergic burden scales. A preoperative high anticholinergic burden is significantly associated with incident delirium [ 40 42 ], although contrary findings with no association have been reported in other studies [ 43 ]. Our study determined that a high anticholinergic burden was significantly associated with POD in both univariable and multivariable analyses.…”
Section: Discussionmentioning
confidence: 98%
“…Still, subgroup analysis showed 80% higher incidence of POD with benzodiazepines as compared to dexmedetomidine (Wang et al, 2023). Studies have shown preoperative anticholinergic load is an independent risk factor for development of POD (Mueller et al, 2020;Herrmann et al, 2022). In post-CABG patients, increased intubation time and duration of surgery are the two largest statistically significant risk factors (Greaves et al, 2020).…”
Section: Postoperative Delirium Risk Factorsmentioning
confidence: 99%
“…[ 32 ] Elderly patients’ exposure to anticholinergic medications increases the risk of POD by 2.7-fold. [ 33 ] Another perioperative risk factor for POD is high glycemic variability. Lin et al .…”
Section: Neurological Complicationsmentioning
confidence: 99%